(untitled) (Research, Society and Development, 2020)
Pulp calcification is commonly found in anterior teeth and in dental elements of older people, being considered a pathological response given by the pulp to injuries suffered by these teeth. Calcifications are associated with trauma, caries and age of the individual, where the root canal is totally or partially obliterated by deposition of mineral tissue. The objective of this work was to carry out an integrative review of the current literature on Guided Endodontics (EG) in teeth with root calcification, highlighting its performance technique, indications, limitations, advantages and disadvantages. An integrative literature review was carried out by searching scientific articles in the electronic database PubMed using the descriptors: guided endodontics, access, root calcification, indexed in the period from 2014 to 2019 that dealt with case reports, in vitro study and ex vivo. After the eligibility criteria, 11 articles published in English were analyzed. Studies have shown that the technique brings more safety to endodontic intervention in teeth with calcification, decreasing the chances of iatrogenesis, such as perforations. The guided access for the endodontic treatment of teeth with root calcification demonstrated high reliability, allowing a more predictable and quick root canal location, in addition to providing a conservative access, with relatively minor dentinal damage, optimizing the treatment.